Endothelium-Derived C-Type Natriuretic Peptide Contributes to Blood Pressure Regulation by Maintaining Endothelial Integrity. Issue 2 (February 2017) - Nakao, Kazuhiro; Kuwahara, Koichiro; Nishikimi, Toshio; Nakagawa, Yasuaki; Kinoshita, Hideyuki; Minami, Takeya; Kuwabara, Yoshihiro; Yamada, Chinatsu; Yamada, Yuko; Tokudome, Takeshi; Nagai-Okatani, Chiaki; Minamino, Naoto; et al.
Abstract : We previously reported the secretion of C-type natriuretic peptide (CNP) from vascular endothelial cells and proposed the existence of a vascular natriuretic peptide system composed of endothelial CNP and smooth muscle guanylyl cyclase-B (GC-B), the CNP receptor, and involved in the regulation of vascular tone, remodeling, and regeneration. In this study, we assessed the functional significance of this system in the regulation of blood pressure in vivo using vascular endothelial cell–specific CNP knockout and vascular smooth muscle cell–specific GC-B knockout mice. These mice showed neither the skeletal abnormality nor the early mortality observed in systemic CNP or GC-B knockout mice. Endothelial cell–specific CNP knockout mice exhibited significantly increased blood pressures and an enhanced acute hypertensive response to nitric oxide synthetase inhibition. Acetylcholine-induced, endothelium-dependent vasorelaxation was impaired in rings of mesenteric artery isolated from endothelial cell–specific CNP knockout mice. In addition, endothelin-1 gene expression was enhanced in pulmonary vascular endothelial cells from endothelial cell–specific CNP knockout mice, which also showed significantly higher plasma endothelin-1 concentrations and a greater reduction in blood pressure in response to an endothelin receptor antagonist than their control littermates. By contrast, vascular smooth muscle cell–specific GC-B knockout mice exhibited blood pressures similar to control mice, and acetylcholine-induced vasorelaxation was preserved in their isolated mesenteric arteries. Nonetheless, CNP-induced acute vasorelaxation was nearly completely abolished in mesenteric arteries from vascular smooth muscle cell–specific GC-B knockout mice. These results demonstrate that endothelium-derived CNP contributes to the chronic regulation of vascular tone and systemic blood pressure by maintaining endothelial function independently of vascular smooth muscle GC-B. Abstract : Supplemental Digital Content is available in the text.